Senior clinical and business managers' perspectives on the influence of different funding mechanisms, and barriers and enablers to implementing models of employing General Practitioners in or alongside emergency departments: Qualitative study. Issue 4 (April 2021) - Choudhry, Mazhar; Edwards, Michelle; Cooper, Alison; Anderson, Pippa; Carson-Stevens, Andrew; Cooke, Matthew; Dale, Jeremy; Hibbert, Peter; Hughes, Thomas; Porter, Alison; Rainer, Timothy; Siriwardena, Aloysius Niroshan; et al.
Highlights: UK Emergency department waiting times and crowding have recently been increasing. Policy has been introduced to employ GPs in emergency departments. We explored senior managers' experiences of implementing this policy. Success was often reliant on unified funding and using local experienced GPs. The policy did not fit all services, local adaptations were needed. Abstract: Purpose: Health policy in England has advocated the use of primary care clinicians at emergency departments to address pressures from rising attendances. This study explored senior managers' perspective son funding mechanisms used to implement the policy and experiences of success or challenges in introducing GPs in or alongside emergency departments. Methods: The perspectives of senior clinical, business and finance managers with responsibility for emergency department services and on-site primary care service implementation were investigated in semi-structured interviews with 31 managers at 12 type-1 emergency departments in England and Wales (February 2018 - September 2019). Emergency departments operated one of three GP models or had prior experience of implementing a GP model. Interviews were thematically analysed. Results: Perceived successful GPs models in emergency departments were reliant on well-organised and unified funding mechanisms, appropriate staffing and governance, and consideration of population demands and needs. Funding mechanisms and the flow of funds were reported as complex, especially in Inside-parallel GP models. The most efficient mechanisms were described at departments where funding was unified, in collaboration with health and community care services. Staffing with local, experienced GPs was important. There were cautions from experiences with private locum providers. Conclusion: Our findings contribute to debates about implementing policy on how primary care clinicians are effectively and safely deployed in emergency departments and how local context should be considered.